Functions of Stress-Induced Lipid Droplets in the Nervous System - Islimye, Eva; Girard, Victor; Gould, Alex P. (Frontiers in Cell and Developmental Biology, 2022)
Lipid droplets are highly dynamic intracellular organelles that store neutral lipids such as cholesteryl esters and triacylglycerols. They have recently emerged as key stress response components in many different cell types. Lipid droplets in the nervous system are mostly observed in vivo in glia, ependymal cells and microglia. They tend to become more numerous in these cell types and can also form in neurons as a consequence of ageing or stresses involving redox imbalance and lipotoxicity. Abundant lipid droplets are also a characteristic feature of several neurodegenerative diseases. In this minireview, we take a cell-type perspective on recent advances in our understanding of lipid droplet metabolism in glia, neurons and neural stem cells during health and disease. We highlight that a given lipid droplet subfunction, such as triacylglycerol lipolysis, can be physiologically beneficial or harmful to the functions of the nervous system depending upon cellular context. The mechanistic understanding of context-dependent lipid droplet functions in the nervous system is progressing apace, aided by new technologies for probing the lipid droplet proteome and lipidome with single-cell type precision.